The complete chloroplast genome of Castanopsis carlesii (Hemsl.) Hay. Issue 2 (3rd July 2019) - Sun, Rong-Xi; Ye, Xue-Min; Wang, Zhen-Li; Lin, Xiao-Fan
Abstract: Castanopsis carlesii (Hemsl.) Hay. is a widely distributed and dominant tree species with significant ecological and economical values. In this study, the complete chloroplast genome sequence of C. carlesii was reported using the Illumina Hiseq 2500 platform. The complete chloroplast genome was 160, 205 bp forming a typical quadripartite structure, with a pair of inverted repeated (IRs) regions of 25, 670 bp, a large single copy (LSC) region of 89, 849 bp, and a small single copy (SSC) region of 19, 016 bp. A total of 124 functional genes were annotated, including 79 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The ML phylogenetic analysis showed that the genus Castanopsis formed a clade except Castanopsis fargesii .